Hyperglycemia Diverts Dividing Osteoblastic Precursor Cells to an Adipogenic Pathway and Induces Synthesis of a Hyaluronan Matrix That Is Adhesive for Monocytes - Wang, Aimin (American Society for Biochemistry and Molecular Biology, 2014)
Isolated rat bone marrow stromal cells cultured in osteogenic medium in which the normal 5.6 mm glucose is changed to hyperglycemic 25.6 mm glucose greatly increase lipid formation between 21–31 days of culture that is associated with decreased biomineralization, up-regulate expression of cyclin D3 and two adipogenic markers (CCAAT/enhancer binding protein α and peroxisome proliferator-activated receptor γ) within 5 days of culture, increase neutral and polar lipid synthesis within 5 days of culture, and form a monocyte-adhesive hyaluronan matrix through an endoplasmic reticulum stress-induced autophagic mechanism. Evidence is also provided that, by 4 weeks after diabetes onset in the streptozotocin-induced diabetic rat model, there is a large loss of trabecular bone mineral density without apparent proportional changes in underlying collagen matrices, a large accumulation of a hyaluronan matrix within the trabecular bone marrow, and adipocytes and macrophages embedded in this hyaluronan matrix. These results support the hypothesis that hyperglycemia in bone marrow diverts dividing osteoblastic precursor cells (bone marrow stromal cells) to a metabolically stressed adipogenic pathway that induces synthesis of a hyaluronan matrix that recruits inflammatory cells and establishes a chronic inflammatory process that demineralizes trabecular cancellous bone.